2016
DOI: 10.1016/j.jad.2015.12.016
|View full text |Cite
|
Sign up to set email alerts
|

The temporal course and clinical correlates of subjective impulsivity in bipolar disorder as revealed through ecological momentary assessment

Abstract: Background Impulsivity is frequently linked with bipolar disorder and is associated with mania and negative outcomes. The temporal dynamics of subjective impulsivity are unclear, in particular whether impulsivity precedes or follows changes in positive or negative affect. Methods A total of 41 outpatients with bipolar disorder (I or II) were provided with mobile devices for 11 weeks and completed twice-daily surveys about affective states and subjective impulsivity. We examined the association between aggreg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
60
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(64 citation statements)
references
References 31 publications
1
60
3
Order By: Relevance
“…Depending on the research question, these assessments may be event‐based, time‐based, or randomly prompted. EMA possesses a number of advantages over typical point‐in‐time assessments, which include: (1) the reduction of retrospective recall biases, (2) the ability to model within‐person trends over time, (3) the assessment of temporal sequences among theoretically‐linked constructs (Depp et al, ; Depp et al, ), (4) the generation of more stable estimates of constructs for outcomes research (Moore, Depp, Wetherell, & Lenze, ), (5) the capacity to monitor treatment response or progress in real‐time, and (6) the assessment of phenomena as they occur in real‐world settings. The ability to assess fluctuation and change in affect, personality, and behavior over time, known as dynamic processes, represents one of the greatest strengths of EMA.…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the research question, these assessments may be event‐based, time‐based, or randomly prompted. EMA possesses a number of advantages over typical point‐in‐time assessments, which include: (1) the reduction of retrospective recall biases, (2) the ability to model within‐person trends over time, (3) the assessment of temporal sequences among theoretically‐linked constructs (Depp et al, ; Depp et al, ), (4) the generation of more stable estimates of constructs for outcomes research (Moore, Depp, Wetherell, & Lenze, ), (5) the capacity to monitor treatment response or progress in real‐time, and (6) the assessment of phenomena as they occur in real‐world settings. The ability to assess fluctuation and change in affect, personality, and behavior over time, known as dynamic processes, represents one of the greatest strengths of EMA.…”
Section: Introductionmentioning
confidence: 99%
“…ESM assesses participants in their normal daily environment, thereby increasing ecological validity; repeatedly assesses participants in the moment, thereby decreasing retrospective bias; and allows for the examination of context of experience. Several studies have employed ESM to examine associations of impulsivity with psychopathology in daily life, including nonsuicidal self‐injury (Bresin, Carter, & Gordon, ), disordered eating (Engel et al, ; Myers et al, ; Steiger, Lehoux, & Gauvin, ), alcohol use (Simons, Dvorak, Batien, & Wray, ; Simons, Gaher, Oliver, Bush, & Palmer, ), bipolar disorder (Depp et al, ), attention‐deficit/hyperactivity disorder (Rosen & Factor, ), and borderline personality disorder (Tomko et al, ). Sperry, Lynam, Walsh, Brown, and Kwapil () examined the original UPPS model and found that, in general, facets were differentially expressed in daily life.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of DHTs described in the selected studies (14 of 18 [77.8%]) were mobile/smartphone apps that collected patient data in real time. In five studies, mobile device apps were used to collect ecological momentary assessments (EMAs) 32,34,38,41,42. In three studies, smartphone apps were used for daily mood and symptom monitoring 26,37,40.…”
Section: Resultsmentioning
confidence: 99%
“…Scores on MZ items were validated against established self- report questionnaires. In the third example of a smartphone-based app for monitoring patients with bipolar disorder, users completed a web-enabled survey of current momentary mood and related experiences 38. The data were used to assess impulsivity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation